2019
DOI: 10.1186/s12889-019-7250-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of e-cigarettes among nursing students: results from a cross-sectional survey in north-eastern Italy

Abstract: Background Data on electronic cigarette (e-cigarette) use among health professional students, who can play a central role in promoting healthy habits and smoking cessation, are sparse. Moreover, the association between e-cigarettes and smoking habits is still debated. The present study aimed to investigate the diffusion of e-cigarette use among nursing students in north-eastern Italy and explore its association with tobacco smoking. Methods In 2015, a questionnaire focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
8
17
0
3
Order By: Relevance
“…In a study by Etter JF [23], 10% of long-term vapers had already tried to quit vaping, and 34% declared an intention to quit vaping in the future. In a study by Canzan et al e-cigarette use was not associated with smoking cessation in nursing students in Italy [37]. Similar results were observed in our study among university students.…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Etter JF [23], 10% of long-term vapers had already tried to quit vaping, and 34% declared an intention to quit vaping in the future. In a study by Canzan et al e-cigarette use was not associated with smoking cessation in nursing students in Italy [37]. Similar results were observed in our study among university students.…”
Section: Discussionsupporting
confidence: 92%
“…E-cigarette use among participants in our study was more prevalent in older age group, male students, higher college class, students who have ≥ 1 close friend who smokes, family history of smoking, and housemates who smoked E-cigarettes. This is partially in accordance with Canzan et al who stated that E-cigarette use was associated with housemates' smoking habits, male sex but not with a family history of smoking and university class [17]; but it is not in agreement with Jiang et al who found that there was non-significant difference between males and females regarding E-cigarette use [18]. It is in agreement with Almutham et al who stated that E-cigarette smoking had a significant correlation with having a family member or a close friend who smokes E-cigarettes [19].…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with a study done by Romijnders et al in which social environment, for example a friend, a father, or a mother who uses E-cigarette, was an initiator for E-cigarette use [ 21 ]. Another study stated that E-cigarette use is affected by sex but not affected by age [ 17 ]. This supports the concept that any family member or friend (social environment) who uses E-cigarette is an initiative for starting its use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of 38 studies implied the odds of quitting traditional cigarettes were 28.0% lower in those who used e-cigarettes than in those who did not 27 . Another study indicated that e-cigarette ever use was associated with a higher risk of starting smoking and with a lower risk of quitting smoking among nursing students 28 . Loukas et al 29 conducted a study among university students and reported that cigarette users who also used e-cigarettes were no more likely than cigaretteonly users to attempt to quit smoking cigarettes.…”
Section: Discussionmentioning
confidence: 99%